Impact of Activities of Women: Special References to Mahila Mandals: Examining the Decline of Women's Status in Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Since ancient times women were given an important place in Indian society. They were treated as Goddess and their presence was essential in family functions especially in Haryana. With the passage of time the status of women in Haryana has been gradually deteriorated. Women especially in rural sector are disorganised resulted in a disadvantaged group despite the glorious tradition of their high status in the family or community. They have been facing discrimination in the male dominated society. The different types of discrimination namely violence at home and in society, sex trafficking, unequal pay and denial of property rights and restrictive customs on account of gender etc. It is important to understand that the only difference between men and women are the gender/biological. All other differences are made socially and sanctioned by the society. Over time it becomes the norm/parampara and the way of life. For example, in some rural as well as in urban areas, it is an accepted fact that: